Living with divine discomfort. : The beauty of a life of folly - Thesnaar, Christo (Stellenbosch Theological Journal, 2019)
It is clear that within the modern age we live, that our tendency is more to live for ourselves than for the others we encounter in our families, communities or societies. In this regard it is timely to explore whether it is a folly that I can only experience the beauty of life when I live in comfort with myself and with those whom I choose to live with. Alternatively, if we embody relationship in our meetings with others, we will always experience discomfort as responsibility, accountability and justice are central within relationships. In this regard, we are interconnected and interdependent to one another and therefore we need to be hospitable to one another. As liturgy is relational in its being it should be a service to justice. In this regard we will experience the beauty of a life of folly.